THE SOCIOLINGUISTIC POSITION OF PALEMBANG RELIGIOUS POETRY - Nasution, Rita Farida (Magistra Andalusia: Jurnal Ilmu Sastra, 2024)
This article examines the sociolinguistic position of Palembang religious poetry in the Palembang speech community in South Sumatra, Indonesia. The Palembang language is unique in that it is used as a language of wider communication and listed as level 3 on EGIDS, yet it does not have an official writing system. Until this study, no academic research on Palembang religious poetry had ever been conducted. This research examines the use of Palembang religious poetry by Palembang people. Ethnographic research methods were employed, and poets and poetry users from various backgrounds and ages were interviewed. Palembang traditional poetry called pantun is also discussed. Findings reveal the origins and the types of religious poetry. Research highlights five poems: three autogenic poems and two translated poems. Three poems are considered spoken poetry and two poems are sung. Poets and poetry users of Palembang religious poetry in this research consist of four men and three women ranging from 25-65 years of age. There are examples of Palembang religious poetry undergoing language shift but it is clear that poetry has strong connections to ethnic identity and language pride.